The Relationship between Transpiration and Calcium Fertilization on Mangosteen (Garcinia mangostana L.) Seedlings - Akmal, Ajmir; Santosa, Edi; Poerwanto, Roedhy; Yunus, Ismadi; Handayani, Rd. Selvy (Journal of Tropical Horticulture, 2018)
The availability of nutrients in plants depends on the ability of plants to absorb nutrients from the soil. One of the processes absorbed by plants is by the presence of the transpiration process.Â  Good transpiration will provide enough nutrients for plants which increase the productivity and quality of mangosteen. One of the quality standards of mangosteen fruit for export quality is the free from yellow sap contamination. It can be possible that transpiration can improve the quality of mangosteen fruit by applying fertilization. In this study Ca fertilization was carried out on mangosteen seeds, where this study aims to investigate the effectiveness of Ca uptake by mangosteen plants with the level of water loss by transpiration. This research was conducted in November 2016-March 2017 at the Leuwikopo Experimental Garden, Bogor Agricultural University. Morphological observations were carried out in its Experimental Garden and the Postharvest Laboratory whileanalysis of calcium content of plant tissue was done at the Department of Agronomy and Horticulture, Bogor Agricultural University. Data obtained then were analyzed using ANOVA test. If the results were significant, Duncan Multiple Range Test (DMRT) was then tested at 0.05 probability level. The results revealed that the transpiration rate of mangosteen plants from several treatments showed a significant difference, the transpiration rate was higher, especially in fertilized plants. The size of the 12th leaf, plants treated with fertilizer have a larger size than the treatment without fertilization. Fertilizing and providing enough water can maintain the growth of the plants.